2006
DOI: 10.1634/stemcells.2006-0442
|View full text |Cite
|
Sign up to set email alerts
|

p66Shc/Notch-3 Interplay Controls Self-Renewal and Hypoxia Survival in Human Stem/Progenitor Cells of the Mammary Gland Expanded In Vitro as Mammospheres

Abstract: The comprehension of the basic biology of stem cells is expected to provide a useful insight into the pathogenesis of cancer. In particular, there is evidence that hypoxia promotes stem cell renewal in vitro as well as in vivo. It therefore seems reasonable that stem cell survival and hypoxia response are strictly connected at molecular level. We here report that the 66-kDa isoform of the SHC gene (p66Shc) is induced in a breast cancer cell line by the exposure to hypoxic environment and that it controls the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
168
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(178 citation statements)
references
References 31 publications
7
168
3
Order By: Relevance
“…Even though our results showed that JAG2 was responsible for a large fraction of the Notch activity under hypoxia, silencing of JAG2 did not result in complete inhibition of the hypoxic potentiation of Notch signaling. In light of the previous reports, the remaining elevation in Notch activity could be due to direct HIF-icN1 interactions or elevation of other Notch receptors (36).…”
Section: Discussionmentioning
confidence: 69%
“…Even though our results showed that JAG2 was responsible for a large fraction of the Notch activity under hypoxia, silencing of JAG2 did not result in complete inhibition of the hypoxic potentiation of Notch signaling. In light of the previous reports, the remaining elevation in Notch activity could be due to direct HIF-icN1 interactions or elevation of other Notch receptors (36).…”
Section: Discussionmentioning
confidence: 69%
“…Then, we tested the impact of the three NRs agonists on MS formation capability, which is currently considered the gold standard assay to assess the breast CSC phenotype in vitro. [6][7][8][9][10][11]33 We found that all the three NRs agonists reduce the number of MCF7-MS, but not of MCF10-MS with respect to control, and that IIF is the most active molecule (Figure 1c and Supplementary Figure 2a). Moreover, we compared the activity of NRs agonists on MS from tumor mammary gland (T-MS) and normal tissue samples (N-MS) ( Table 1 We finally proved that both in normoxia and hypoxia, NRs agonists induce cytotoxic effects in MS (Supplementary Figure 3a) and upregulate their cognate receptors (Supplementary Figure 3b).…”
Section: Resultsmentioning
confidence: 79%
“…This phenomenon is paralleled by the hampering of pro-inflammatory NF-kB/IL6 axis and associates with the downregulation of MS regulatory genes (SLUG, Notch3, Jagged1). 6,7,9,10 We also report that, at variance with the other NRs agonists, the PPARa specific agonist WY exerts a promoting role on MS formation and on the accompanying pro-inflammatory phenotype.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations